2014
DOI: 10.1113/jphysiol.2013.267476
|View full text |Cite
|
Sign up to set email alerts
|

Slowed muscle oxygen uptake kinetics with raised metabolism are not dependent on blood flow or recruitment dynamics

Abstract: Key pointsr A slow adjustment of skeletal muscle oxygen uptake (V O 2 ) to produce energy during exercise predisposes to early fatigue.r In human studies,V O 2 kinetics are slow when exercise is initiated from an elevated baseline; this is proposed to reflect slow blood flow regulation and/or recruitment of muscle fibres containing few mitochondria.r To investigate this, we measuredV O 2 kinetics in canine muscle, with experimental control over muscle activation and blood flow.r We found thatV O 2 kinetics rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 52 publications
3
29
0
Order By: Relevance
“…However, the dynamics of the NIRS-derived [HHb] signal was shown to adjust (τ[HHb]) at a slower rate (simultaneous with the dynamic adjustments of V O 2p ) in the US compared to the LS in healthy young (MacPhee et al 2005;Williams et al 2013) and older men (Spencer et al 2011) suggesting that the greater τV O 2p was not related to local O 2 availability. This notion was supported by Wust et al (2014), who demonstrated in the electrically stimulated dog gastrocnemius muscle model that the adjustment of muscle O 2 uptake was slower during transitions to a higher vs. lower stimulation rate despite the pre-transition muscle blood flow and O 2 delivery being increased (via pump-perfusion) to the highest level achieved during a spontaneous control condition. Thus, our data and analysis suggest that blood flow and O 2 delivery to and within the microvasculature are unlikely responsible for slower V O 2p kinetics in the US and, in fact, the balance between microvascular O 2 delivery and utilization appeared to more closely match in US compared to LS.…”
Section: Influence Of O 2 Provisionmentioning
confidence: 82%
“…However, the dynamics of the NIRS-derived [HHb] signal was shown to adjust (τ[HHb]) at a slower rate (simultaneous with the dynamic adjustments of V O 2p ) in the US compared to the LS in healthy young (MacPhee et al 2005;Williams et al 2013) and older men (Spencer et al 2011) suggesting that the greater τV O 2p was not related to local O 2 availability. This notion was supported by Wust et al (2014), who demonstrated in the electrically stimulated dog gastrocnemius muscle model that the adjustment of muscle O 2 uptake was slower during transitions to a higher vs. lower stimulation rate despite the pre-transition muscle blood flow and O 2 delivery being increased (via pump-perfusion) to the highest level achieved during a spontaneous control condition. Thus, our data and analysis suggest that blood flow and O 2 delivery to and within the microvasculature are unlikely responsible for slower V O 2p kinetics in the US and, in fact, the balance between microvascular O 2 delivery and utilization appeared to more closely match in US compared to LS.…”
Section: Influence Of O 2 Provisionmentioning
confidence: 82%
“…; Wüst et al . ). It is not currently possible to know whether the muscle motor units recruited to transition to low work rates are the same or different from those recruited to transition to greater work rates.…”
Section: Discussionmentioning
confidence: 97%
“…(), using a model of incomplete muscle recovery, and by Wüst et al . () with exercise transitions in electrically stimulated dog hindlimb muscle. However, DiMenna et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in the present study, we stress that precedence be given to interpreting the TD and τ of muscle deoxygenation with these preliminary kinetic data supported by the Δdeoxy[Hb+Mb]/ΔV̇normalO2 ratio to infer the dynamic (mis)matching between O 2 delivery and utilization. Finally, it should be noted that baseline pedalling during M → VH involved simultaneously raising pre‐transition V̇normalO2 with work rate, which, when both are dissociated, has the potential to influence the τtrueV̇O2normalp and G p via independent mechanisms (Bowen et al., ; DiMenna et al., ; Wust et al., ). Therefore, in the present study, whether an increased baseline work rate per se altered phase II V̇normalO2 kinetics cannot be established.…”
Section: Discussionmentioning
confidence: 99%